The impact of a training program on improving the maximum oxygen consumption and the repeated sprint ability of football players (U19) - BENLABED, Abderrahim; KHELLAF, Mohamed (Journal of Human Sciences, 2020)
This research aims to verify the impact of a training program based on the diversification of training methods during the preparatory phase of the U19 football category on maximum oxygen consumption (vo2max) and the ability to repeat the actions of speeds. The training program is based on the continuous method, the fartlek, the intermittent and the reduced games used by many specialists of the field cited by ALEXANDER DELLAL in his book "A season of physical preparation". The VAMEVAL test is used to measure the maximum aerobic speed (VMA) and the maximum oxygen consumption (vo2max). The 12x20 m test to measure the speed retention index (RSA). The results show that the program used has a positive effect by improving both the maximum oxygen consumption and the ability to repeat the speeds.